2022
DOI: 10.3390/pharmaceutics14020385
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Administration of Imiquimod Promotes T and B Cell Differentiation into Effector Cells or Plasma Cells

Abstract: We are interested in promoting the development of transcutaneous immunization using microneedle technology and attempting to apply an adjuvant with transcutaneous immunization to improve the efficacy and reduce the amount of antigen and number of administrations needed. In this study, we collected basic information to help elucidate the mechanism responsible for the transcutaneous adjuvant activity of imiquimod (IMQ), which is a ligand of toll-like receptor (TLR) 7. In mouse groups administered ovalbumin (OVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…In some of these, lupus results from direct variation of TLR7 gene dose, or enhanced nucleic acid sensing function. These models include BXSB Yaa mice that harbour a chromosomal segment duplication from X onto Y that contains TLR7 ( Pisitkun et al, 2006 ; Soni et al, 2014 ) , Tlr7 transgenic (tg) mice ( Walsh et al, 2012 ), TLR7-agonist (imiquimod) induced lupus ( Hirobe et al, 2022 ; Voss et al, 2022 ), and kika mice that carry a TLR7 gain-of-function variant found in a girl with SLE ( Brown et al, 2022 ). In another group of lupus models in which Tlr7 gene expression is intact, disease pathogenesis is also dependent on TLR7 signaling.…”
Section: Evidence Of Gc-independent Systemic Autoimmunitymentioning
confidence: 99%
“…In some of these, lupus results from direct variation of TLR7 gene dose, or enhanced nucleic acid sensing function. These models include BXSB Yaa mice that harbour a chromosomal segment duplication from X onto Y that contains TLR7 ( Pisitkun et al, 2006 ; Soni et al, 2014 ) , Tlr7 transgenic (tg) mice ( Walsh et al, 2012 ), TLR7-agonist (imiquimod) induced lupus ( Hirobe et al, 2022 ; Voss et al, 2022 ), and kika mice that carry a TLR7 gain-of-function variant found in a girl with SLE ( Brown et al, 2022 ). In another group of lupus models in which Tlr7 gene expression is intact, disease pathogenesis is also dependent on TLR7 signaling.…”
Section: Evidence Of Gc-independent Systemic Autoimmunitymentioning
confidence: 99%